Structural and sensory impact of various emulsifiers in cocoa hazelnut spread formulations - Icyer, Necattin Cihat; Ozmen, Duygu; Sener, Dilek; Kokyar, Nagihan; Toker, Omer Said (WILEY, 2024)
In this study, the effects of emulsifiers such as lecithin, AMPs, Palsgaard (R) Oil-Binder and GMS on cocoa hazelnut spread rheology were compared under the same process conditions and formulation. Emulsifiers were added to the formulation separately at rates of 0.3%-0.4%-0.5%. Hardness values in cocoa hazelnut spread were examined at 15-day intervals until the 60th day. In addition, viscosity, rheological analyses, color, spreadability, stability tests, and sensory analyses were performed. In the production of cocoa hazelnut spread, lecithin and AMP have less hardness and lower viscosity, greater fluent consistency, better spreadability, and lower work of shear values compared with other emulsifiers. The emulsifier type/ratio difference did not affect the color value statistically. It was determined that the use of Oil-Binder and GMS significantly protected the stability compared with other emulsifiers. During the 60-day storage period, lecithin preserved its hardness properties better than other emulsifiers. When sensory properties were examined, the use of lecithin and AMP in cocoa hazelnut spread samples scored high in brightness, spreadability, mouthfeel, and taste parameters. As a result, lecithin comes to the fore in the use of different types and ratios of emulsifiers in cocoa hazelnut spread production technology.
Keywords: Cocoa hazelnut spread; emulsifier; lecithin; rheology; Food Science & Technology